ANALISIS KELAYAKAN USAHA TERNAK SAPI POTONG DI KECAMATAN RAIMANUK KABUPATEN BELU (Feasibility analysis of beef cattle business in Raimanuk Sub-District of Belu) - Theofila S.R. Taek; Ulrikus Romsen Lole; Arnoldus Keban (Universitas Nusa Cendana, 2021)
This study aims to were: 1) to know the amount of income farmers in the business of beef cattle in the District Raimanuk. 2) to know the feasibility of beef cattle business in Raimanuk District. Sampling is done through two stages. The first stage is the determination of sample villages conducted by purposive sampling and the second stage is the determination of the respondents who made a simple random. The data were collected using interview technique. The data collected includes primary and secondary data. Primary data obtained from observation and interview, while secondary data obtained from related institutions and literature related to research. The analysis is done by using income analysis and financial analysis. The results showed that the income earned by each cattle rancher amounted to Rp10.318.759/year and the financial investment criteria such as NPV Rp7. 561.847, Net B/C 1.96, IRR 23%, and PBP 2.96 years.